2000
DOI: 10.1210/jc.85.12.4568
|View full text |Cite
|
Sign up to set email alerts
|

Differential Genetic Alterations in von Hippel-Lindau Syndrome-Associated and Sporadic Pheochromocytomas

Abstract: Pheochromocytomas arise sporadically and as a component tumor of the inherited cancer syndromes von Hippel-Lindau disease (VHL), multiple endocrine neoplasia type 2 (MEN 2), and type 1 neurofibromatosis. Germline mutations of the VHL tumor suppressor gene (VHL) are responsible for VHL, and germline RET protooncogene mutations are associated with MEN 2. The present study was conducted to examine a large series of 36 VHL-related pheochromocytomas for somatic VHL and RET gene alterations and loss of heterozygosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
50
0
4

Year Published

2001
2001
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 0 publications
10
50
0
4
Order By: Relevance
“…showed that the LOH at 3p was detected in 91% PHE with VHLD; this value was relatively high when compared with 24% incidence observed with the LOH at 3p in sporadic PHE [24]. This is in agreement with the result of our present study.…”
Section: Discussionsupporting
confidence: 93%
“…showed that the LOH at 3p was detected in 91% PHE with VHLD; this value was relatively high when compared with 24% incidence observed with the LOH at 3p in sporadic PHE [24]. This is in agreement with the result of our present study.…”
Section: Discussionsupporting
confidence: 93%
“…VHL is considered a classical tumor suppressor gene in the sense that, in accordance with Knudsons two-hit model, biallelic inactivation is usually required for tumorigenesis (Knudson 1971(Knudson , 1996. Loss of heterozygosity (LOH) of the wild-type allele is frequent in VHL-associated tumors, including PCCs (Crossey et al 1994), and hypermethylation of the wild-type allele as an alternative mechanism of gene inactivation has also been reported (Herman et al 1994, Prowse et al 1997, although not in PCCs (Bender et al 2000). Disease-causing mutations in VHL can be missense, nonsense, as well as deletions and insertions (indels), with missense mutations being more frequent in families with PCC/PGL (Woodward & Maher 2006).…”
Section: Ret-associated Pccs and Pglsmentioning
confidence: 99%
“…Loss of heterozygosity (LOH) and comparative genomic hybridization (CGH) studies performed by us and others have reported allelic losses at 1p, 3pq, 17p, and 22q, but corresponding genes have not been identified. [3][4][5][6] Particularly 17p, the chromosome arm where the p53 gene is located, is interesting to investigate knowing that aberrations in this gene are implicated in many inherited and sporadic forms of malignancy, such as colon, lung, brain, and breast tumors. 7 p53 is functionally involved in guarding the stability of the genome.…”
mentioning
confidence: 99%